Changes in Emergency Medical Services Before and During the COVID-19 Pandemic in the United States, January 2018–December 2020. (6th May 2021) - Handberry, Maya; Bull-Otterson, Lara; Dai, Mengtao; Mann, N Clay; Chaney, Eric; Ratto, Jeff; Horiuchi, Kalanthe; Siza, Charlene; Kulkarni, Aniket; Gundlapalli, Adi V; Boehmer, Tegan K
Abstract: Background: As a result of the continuing surge of coronavirus disease 2019 (COVID-19), many patients have delayed or missed routine screening and preventive services. Medical conditions, such as coronary heart disease, mental health issues, and substance use disorder, may be identified later, leading to increases in patient morbidity and mortality. Methods: National Emergency Medical Services Information System data were used to assess 911 emergency medical services (EMS) activations during 2018–2020. For specific activation types, the percentage of total activations was calculated per week, and Joinpoint analysis was used to identify changes over time. Results: Since March 2020, the number of 911 EMS activations has decreased, while the percentages of on-scene death, cardiac arrest, and opioid use/overdose EMS activations were higher than prepandemic levels. During the early pandemic period, percentages of total EMS activations increased for on-scene death (from 1.3% to 2.4% during weeks 11–15), cardiac arrest (from 1.3% to 2.2% during weeks 11–15), and opioid use/overdose (from 0.6% to 1.1% during weeks 8–18). The percentages then declined but remained above prepandemic levels through calendar week 52. Conclusions: The COVID-19 pandemic has indirect consequences, such as relative increases in EMS activations for cardiac events and opioid use/overdose, possibly linked to disruptions is healthcare access and health-seeking behaviors. Increasing telehealth visits and other opportunities for patient–provider touch points for chronic disease and substance use disorders that emphasize counseling, preventive care, and expanded access to medications can disrupt delayed care-seeking during the pandemic and potentially prevent premature death.